2021
DOI: 10.1182/blood.2020008750
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab vs rituximab for advanced DLBCL: a PET-guided and randomized phase 3 study by LYSA

Abstract: Rituximab plus polychemotherapy is standard of care in diffuse large B-cell lymphoma (DLBCL). GAINED trial compares obinutuzumab to rituximab. GAINED (NCT01659099) is an open-label, randomized phase 3 trial. Transplant-eligible patients (18-60yrs) with untreated aged-adjusted international prognostic index (aaIPI) ≥1 DLBCL were randomized (1:1) between obinutuzumab or rituximab. Patients were stratified by aaIPI (1; 2-3) and chemotherapy regimen (ACVBP; CHOP). Consolidation treatment was determined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 28 publications
4
79
0
Order By: Relevance
“…To validate the prognosis value of ncMO obtained on this training cohort, we analyzed by flow cytometry the proportion of monocyte subsets in an independent cohort of 155 DLBCL samples from the recently published GAINED trial (NCT01659099). 24 With the previously calculated thresholds, high proportion of ncMO and high absolute count of ncMO was associated with a lower overall survival (P = .017 and P = .011, respectively) (Figure 5A and Figure S8B). A univariate analysis on the validation cohort showed that Ann Arbor Stage III-IV, ECOG status >1, elevated LDH, PET4 positivity, and increase in circulating ncMO were associated with lower OS (Table S4).…”
Section: High Level Of Circulating Ncmo Is Correlated With An Adverse Prognosis In Dlbclsupporting
confidence: 52%
See 1 more Smart Citation
“…To validate the prognosis value of ncMO obtained on this training cohort, we analyzed by flow cytometry the proportion of monocyte subsets in an independent cohort of 155 DLBCL samples from the recently published GAINED trial (NCT01659099). 24 With the previously calculated thresholds, high proportion of ncMO and high absolute count of ncMO was associated with a lower overall survival (P = .017 and P = .011, respectively) (Figure 5A and Figure S8B). A univariate analysis on the validation cohort showed that Ann Arbor Stage III-IV, ECOG status >1, elevated LDH, PET4 positivity, and increase in circulating ncMO were associated with lower OS (Table S4).…”
Section: High Level Of Circulating Ncmo Is Correlated With An Adverse Prognosis In Dlbclsupporting
confidence: 52%
“…22 Prognosis scores were validated in a second cohort of 155 DLBCL patients from the recently published GAINED trial (ClinicalTrials.gov Identifier: NCT01659099). 24 Clinical characteristics of DLBCL patients enrolled in this validation cohort are listed in Table 1. Finally, we reanalyzed CyTOF data (Flow Repository FR-FCM-Z2CA, already published by our group) 23 from myeloid cells from DLBCL tumors (n = 7).…”
Section: Samplesmentioning
confidence: 99%
“…Large B-cell (R/R) DLBCL Axi-cel (ZUMA-1) [10] Tisa-cel (JULIET) [11] Liso-cel (TRANSCEND) [9] 1st line (high-risk): Axi-cel (ZUMA-12) [37] 2nd line: Axi-cel (ZUMA-7) [35] , Tisa-cel (BELINDA) [36] , Liso-cel (TRANSFORM) CAR T plus (R/R): Axi-cel (ZUMA-6; atezolizumab) [54] , Tisa-cel (PORTIA; pembrolizumab) [55] , Tisa-cel (NCT03876028; ibrutinib), Liso-cel (PLATFORM; durvalumab, CC-122/220) Allogeneic CAR (R/R): ALLO-501A (ALPHA-2), CAR-NK (NCT03056339) [62] HGBCL…”
Section: Lymphoma Fda-approved Additional Histologies Included In Pivotal Trials Highlighted Ongoing Studiesmentioning
confidence: 99%
“…However, there may be a population of patients at high risk of relapse who benefit from even earlier administration of CAR T-cells, although identifying these patients in the upfront setting can be challenging. ZUMA-12 is an ongoing phase 2, multicenter, open-label single arm study of axi-cel in patients with high risk large B-cell lymphoma who have a positive interim PET after 2 cycles of standard frontline chemoimmunotherapy [37] . For the 12 response-evaluable patients in a planned interim analysis, the ORR was 92% with a CR rate of 75%, and 75% of patients had ongoing responses at data cut off.…”
Section: Dlbcl and Other Large B-cell Lymphomasmentioning
confidence: 99%
“…Therapy efficacy is continuously improving in MCL, through the optimization of chemotherapy-based standards of care 1 or the recent development of chemo-free targeted therapy combinations. 2,3 Nevertheless, MCL is still considered incurable due to iterative relapses. In addition, MCL patients present heterogeneous clinical courses from indolent to very high risk, the early identification of the latest being a central question in the field nowadays.…”
mentioning
confidence: 99%